Probelamtika Pembelajaran Bahasa Arab Melalui Aplikasi Google Meet dan Solusi Pemecahannya - Mahmudin, Wildan (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Offline and online have become an academic atmosphere that has been carried out in the learning process, especially after the emergence of the covid-19 pandemic. Many problems arise in the implementation of online Arabic learning through the Google meet application, and these problems are mainly related to non-linguistics such as motivation, infrastructure, and others. Therefore, researchers are interested in conducting research related to the Problems of Learning Arabic through the Google Meet Application and at the same time exploring solutions to overcome these problems. The purpose of the research is to find out the implementation, prolematics and solution solutions in Arabic language learning through the use of the Google Meet application in the PAI Study Program Level I IAIT Tasikmalaya. This research was conducted using a qualitative descriptive method, where the researcher took data through interviews with Arabic language lecturers and first-level PAI IAIT students. The results of this study are: 1) Learning is carried out according to the RPS and lecture schedule with the method often used is the sermon or lecture method and evaluates after before closing the lesson. 2) The problems obtained are: a) Incomprehensive understanding of the material; b) The limitations of lecturers in the ability to use the Google Meet application; c) Students are not controlled optimally during learning; d) Weak internet network. 3) To overcome these problems, the lecturers make various efforts with full creativity and innovation in realizing effective online Arabic learning.